A comunicação entre a inervação simpática e os receptores β-adrenérgicos contribui para a hipertrofia cardíaca pós-natal - Marcos Eliezeck dos Santos Inacio (2022)
Cardiac maturation can be understood as a set of changes in gene expression, metabolic profile and in the structure of the fetal cardiomyocyte (CM), until this cell reaches an adult phenotype. The maturation process is basically divided into periods, the pre, peri and post natal periods. Cardiac hypertrophy (CH) is an important step in the process of cardiac maturation, especially during the postnatal period, in which CMs use this process to increase in volume. Adrenergic signaling is a classic system involved in the regulation of hypertrophic cardiac growth. Despite this knowledge, little is known about the contribution of adrenergic signaling in the regulation of postnatal cardiac hypertrophy. Therefore, the main goal of this work was to investigate the role of sympathetic innervation on the cardiac maturation process. All experiments were performed according to the protocols established by the Ethics Committee for the use of animals at the Universidade Federal de Minas Gerais (CEUA 29/2021). Forty mice aged between 1 and 45 days of both sexes were used in this study, and these included wild-type C57BL/6J, strain and genetically engineered FVB.129-Adrb2tm1Bkk/J (B2-KO) (Strain #031496) and Myh7tm1Unc (MGI: 3776012) (Myh7-YFP) mice. Our experimental protocols included treatments with 6-OHDA (100 mg/kg), Atenolol, propranolol, isoproterenol, formoterol or dobutamine (5 mg/kg, subcutaneously). Hearts were collected at P1 (one day after birth), P11, P21 and P45, and used for western blot, immunofluorescence, confocal microscopy and HPLC-ED measurements. Statistical analysis was performed using the t-Student or One-Way ANOVA test. We first temporally characterized the maturation of adrenergic signaling in the heart of C57BL/6J mice. BDNF and NGF, neurotrophins involved in neuronal growth, peaked in the heart at P1 and P45 respectively. Tyrosine hydroxylase (TH) and Monoaminooxidase (MAO), enzymes involved in the synthesis and degradation of noradrenaline (NE), respectively, showed a gradual increase in the expression from P1 to P21, reaching its peak at P45. Likewise, cardiac NE content revealed a similar pattern. Thus, it can be concluded at this point that the cardiac sympathetic innervation undergoes a maturation process in the postnatal period, with the identification of NE and its receptors in P21. With this in mind, we promoted sympathetic denervation by 6-OHDA treatment and assessed CH at P21. 6-OHDA heart showed a reduction in cardiac weight (CW) and cardiomyocyte area at P21, with no impact on other aspects of cardiac maturation, such as cardiomyocyte contractility, T-tubule formation, cell proliferation or downregulation of fetal genes. Strikingly, 6-OHDA treatment induced a decrease in the tetranucleated CM population when compared to control. To further confirm the involved of adrenergic signaling in the control of CM hypertrophy, we treated mice with the β-blocker, propranolol. Blockade of the β-adrenergic receptor (βAR) in mice from P11 to P20 induced a similar reduction in CW and cardiomyocyte area. The participation of postnatal β1AR and β2AR in CH was confirmed when the reduction in cardiomyocyte area promoted by 6-OHDA was prevented by treatment with isoproterenol (non-selective βAR agonist), dobutamine or formoterol, selective β1AR and β2AR agonists, respectively. In conclusion, our data show that cardiac sympathetic innervation undergoes a process of maturation in the postnatal period, with the identification of NE and its receptors in P21. Activation of both β1 and β2 receptors contributes to postnatal CH, reinforcing the importance of sympathetic innervation for cardiac maturation.